Tantangan dan Peluang Pendidikan Islam di Era Digital: Peran Guru dan Strategi Adaptif - Muhammad Rizal (Al-Widad, 2025)
Ideally, digital technology enables equal access to quality education, flexible learning processes, and innovative teaching practices. In reality, educational systems still face significant challenges such as unequal technological infrastructure, limited digital competence among teachers, and negative impacts on students’ learning behavior and character. This study aims to analyze the challenges and opportunities of education in the digital era, focusing on the role of teachers and adaptive strategies to improve learning quality. This research employs a qualitative library research approach by examining relevant academic journals, books, and policy documents related to digital education and instructional technology. The findings indicate that digital transformation enhances learning effectiveness and resource accessibility, yet it simultaneously creates a digital divide and increases teachers’ workload in mastering pedagogical and technological competencies. Teachers play a crucial role as facilitators, motivators, and guides in promoting responsible technology use and meaningful learning experiences. This study contributes to educational discourse by offering an integrated perspective on how adaptive teacher strategies, continuous professional development, and equitable technological support can optimize the benefits of digital education while minimizing its risks, thereby supporting sustainable and inclusive educational development.